(untitled) (Hoboken, N.J., 2006)
Written for researchers and graduate students, each of the six articles of this volume provide an overview of a question or field, with discussion of its development and current state of research. The topics are dynamical models for two-dimensional infrared spectroscopy of peptides, energy transfer and photosynthetic light harvesting, second and first-order phase transitions in molecular nanoclusters, calculus for relating the dynamics and structure of complex biological networks, analysis and control of ultrafast dynamics in clusters, and ultracold large finite systems.
Keywords: Chemistry, Physical and theoretical,Hóa học, vật lý và lý thuyết